Jerk, California - Friesen, Jonathan (New York : Speak, 2008)
Plagued by Tourette's syndrome and a stepfather who despises him, Sam meets an old man in his small Minnesota town who sends him on a road trip designed to help him discover the truth about his life.
Booklist.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Booklist, September 2008.
Library Media Connection, January 2009.
School Library Journal, December 2008.
Keywords: Automobile travel -- Juvenile fiction; Fathers -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Tourette syndrome -- Juvenile fiction; Automobile travel -- Fiction; Fathers -- Fiction; Identity -- Fiction; Interpersonal relations -- Fiction; Tourette syndrome -- Fiction; Automobile travel -- Fiction; Fathers -- Fiction; Identity (Psychology) -- Fiction; Interpersonal relations -- Fiction; Tourette syndrome -- Fiction